P354 Perceived Quality of Care is associated to quality of life, work productivity and gender but not disease phenotype: a prospective study in a high-volume IBD centre. (25th January 2019) - Gonczi, L; Kurti, Z; Verdon, C; Reinglas, J; Kohen, R; Morin, I; Chavez, K; Bessissow, T; Afif, W; Wild, G; Seidman, E; Bitton, A; et al.
Abstract: Background: Measuring the quality of care (QoC) in IBD has become increasingly important, yet complex assessment of quality indicators and perceived quality of care is rare. In this prospective study, we evaluated patients' satisfaction on the QoC using the QUOTE-IBD questionnaire in the context of health related quality of life (HRQoL) and work productivity loss in a tertiary care IBD centre. Methods: Consecutive patients attending McGill University Health Centre (MUHC)-IBD Centre completed the QUOTE-IBD, SIBDQ, IBD-Control and WPAI questionnaires. The QUOTE-IBD comprises 23 items (8 domains) rated for importance (I) and performance (P), then a quality impact (QI) score was calculated (QI = 10-[I*P]) reflecting the overall satisfaction with each item. QI scores were calculated for the evaluation of GP, IBD-specialist and hospital care in each patient. Results of the QUOTE-IBD were compared with demographic data, disease phenotype, SIBDQ, IBD-Control and WPAI questionnaires. Patient clinical data were captured upon completion of the questionnaires. Results: 525 patients (47.1% male, mean age: 41 years, CD: 71.2% [L3: 54.6%, B2/B3: 50.3%], UC: 28.8% [extensive colitis: 55.6%], biological therapy: 55.6%) completed the questionnaire. Total QI scores were similar for GP, IBD-specialists and hospital care (8.57, 8.70 and 8.33, respectively). Lower satisfaction was found regarding accessibility and information on nutrition. In multi-variate analyses, there was no overall difference between the QoC domains provided by the GP and IBD-specialists in either CD or UC ( p = 0.231 and p = 0.061), with the exception of specialised information provided ( p < 0.05). Female gender, poor HRQoL (SIBDQ ≤ 50) and poor disease control (IBD-Control < 13) were associated with significantly lower mean QI scores in multiple domains assessing both GP and IBD-specialists ( p < 0.001 for all). Work productivity loss assessed by WPAI was significantly higher in patients with extensive UC, biological therapy and active disease (each p < 0.05). There was a clear inverse correlation between QI scores and work productivity loss (GP: p = 0.004; IBD-specialist: p < 0.001). Conclusions: Overall satisfaction with QoC was good and not different in GP and IBD-specialist provided care in this large referral IBD cohort. Female gender, poor HRQoL and work productivity loss was strongly correlated with patient satisfaction, highlighting that perceived QoC is subjective to disease control and quality of life.